1998
DOI: 10.1103/physreve.57.1327
|View full text |Cite
|
Sign up to set email alerts
|

Universal short-time behavior of the dynamic fully frustratedXYmodel

Abstract: With Monte Carlo methods we investigate the dynamic relaxation of the fully frustrated XY model in two dimensions below or at the Kosterlitz-Thouless phase transition temperature. Special attention is drawn to the sublattice structure of the dynamic evolution. Short-time scaling behaviour is found and universality is confirmed. The critical exponent θ is measured for different temperature and with different algorithms. PACS: 64.60. Ht, 75.10.Hk, 02.70.Lq, 82.20.Mj Typeset using REVT E X * Work supported in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 30 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…For example, for the XY model at T = 0.70, t mic ∼ 300 − 400. This increase of t mic for lower temperatures was also noticed in the measurements of the critical initial increase of the magnetization [16,17]. This phenomenon is somehow understandable since at low temperatures the configuration tends to be frozen.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…For example, for the XY model at T = 0.70, t mic ∼ 300 − 400. This increase of t mic for lower temperatures was also noticed in the measurements of the critical initial increase of the magnetization [16,17]. This phenomenon is somehow understandable since at low temperatures the configuration tends to be frozen.…”
supporting
confidence: 69%
“…This scenario is very different from that of critical systems with second order phase transitions. [17], while η and z 1 are from Ref. [17].…”
mentioning
confidence: 99%
“…problems, including frustrated and/or random systems [19][20][21][22][23]. It has also been extended beyond second-order transitions; e.g., the KT transition [18,[24][25][26][27] and first-order transition systems [28]. In an NER analysis, the equilibration step is not necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive Monte Carlo ͑MC͒ simulations showed that the short-time dynamic scaling is not only conceptually interesting but also practically important, e.g., it leads to new ways for the determination of the critical exponents and the critical temperature. 20,21 Recently, Franzese et al 22 have studied the phase transitions of the 2D FFXY model on a square lattice with nearest neighbor ͑NN͒ and next-nearest neighbor ͑NNN͒ couplings by analyzing Binder's cumulant of magnetization up to system size Lϭ72. They found that an Ising-like transition and a KT transition coexist when xϽx c ϭ1/ͱ2 and the critical temperatures T c Z 2 and T c U(1) decrease with increasing x, where x is the ratio between NNN and NN couplings.…”
Section: Introductionmentioning
confidence: 99%